Penggunaan Parameter Gerakan Tanah untuk mengidentifikasi Likuifaksi selama Gempa Besar di Thailand Utara - Mase, Lindung Zalbuin (MEDIA KOMUNIKASI TEKNIK SIPIL, 2021)
This paper presents a ground response analysis to simulate the liquefaction phenomenon during the 2011 Tarlay Earthquake in northern Thailand. The site investigation data and geophysical measurements on 7 sites in northern Thailand were collected. The multi-springs element model was implemented in finite element ground response analysis. Several parameters, such as peak ground acceleration, peak ground velocity, amplification factor, excess pore pressure ratio, were observed. Furthermore, the correlation from the ground motion parameters was generated to estimate liquefaction potential, which was represented by excess pore pressure ratio. The result showed that the excess pore pressure ratio was relatively well correlated with several ground parameters, such as amplification factor, velocity-acceleration ratio, and factor of safety against liquefaction. The results could be also used for the engineering practice in predicting liquefaction potential in Northern Thailand.